2010
DOI: 10.1007/s10895-010-0726-x
|View full text |Cite
|
Sign up to set email alerts
|

A New Fluorescent Sensor Based on 1H-pyrazolo[3,4-b]quinoline Skeleton. Part 2

Abstract: A novel fluorescent dye bis-(pyridin-2-yl-methyl)-(1,3,4-triphenyl-1H-pyrazolo[3,4-b]quinolin-6-ylmethyl)-amine (P1) has been synthesized and investigated by means of steady state and time-resolved fluorescence techniques. This compound acts as sensor for fluorescence detection of small inorganic cations (lithium, sodium, barium, magnesium, calcium, and zinc) in highly polar solvents such as acetonitrile. The mechanism which allows application of this compound as sensor is an electron transfer from the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Furthermore, noticeable bathochromic shifts of the fluorescence bands were observed for M 2 Zn 2+ and M 2 Mg 2+ complexes. These findings were explained by the formation of excimer species [M 2+ (MM)]*, which was confirmed by quantum chemical calculations [177]. In 2013, the same research group demonstrated a detailed study on the pyrazoloquinoline derivative PQ 1d, which was a direct precursor for the synthesis of the aza-crown fluorescence probe PQ 1, previously reported by Rurack [5].…”
Section: Application Of Pyrazoloquinolines In Fluorescence Sensingmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, noticeable bathochromic shifts of the fluorescence bands were observed for M 2 Zn 2+ and M 2 Mg 2+ complexes. These findings were explained by the formation of excimer species [M 2+ (MM)]*, which was confirmed by quantum chemical calculations [177]. In 2013, the same research group demonstrated a detailed study on the pyrazoloquinoline derivative PQ 1d, which was a direct precursor for the synthesis of the aza-crown fluorescence probe PQ 1, previously reported by Rurack [5].…”
Section: Application Of Pyrazoloquinolines In Fluorescence Sensingmentioning
confidence: 55%
“…It was found that this compound can act as a highly efficient Since the aforementioned studies on pyrazoloquinoline-based sensors were reported, almost a decade passed until this stem was followed. Then, between 2010 and 2013, Mac and co-workers published a series of articles on ion-sensitive pyrazoloquinolines, which varied by the molecular architecture of the receptor unit (see Figure 16b) [175][176][177]. All of the sensors presented (PQ 1a-d) were designed for PET signalling, and they maintained the connection between the receptor unit and the pyrazoloquinoline chromophore via the non-conjugated methylene spacer.…”
Section: Application Of Pyrazoloquinolines In Fluorescence Sensingmentioning
confidence: 99%
“…Generally, an ideal G-quadruplex fluorescent probe is assumed to consist of a fluorescent signaling unit specifically recognizing the G-quadruplex structure. Pyrazoloquinolines have been shown to be efficient organic emitters, [16][17][18] with applications in fluorescence sensing 19,20 and electroluminescence. 21 Recently, a derivative of this class of compounds showed a selective binding to human telomeric G4 multimers over monomeric ones.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting blue-fluorescent marker for LDs is the commercially available monodansylpentane (MDH), which has been successfully used in multicolor live cell imaging, supporting the importance of the discovery of new markers emitting in this region of the visible spectra. This was not surprising because the pyrazolo skeleton can be found as a subunit together with other moieties such as pyridine, [9] coumarin, [10] quinoline, [11][12][13] and quinoxaline [14] in tri-and tetracyclic molecules that show fluorescent properties. This was not surprising because the pyrazolo skeleton can be found as a subunit together with other moieties such as pyridine, [9] coumarin, [10] quinoline, [11][12][13] and quinoxaline [14] in tri-and tetracyclic molecules that show fluorescent properties.…”
Section: Introductionmentioning
confidence: 99%